Opioid-Related Deaths in Eastern Ontario from 2011 to 2016. Issue 1 (March 2019) - Parai, Jacqueline L.; Castonguay, Krista; Milroy, Christopher M.
There has been a growing opioid crisis in the United States and Canada. The aim of this study was to analyze trends in opioid-related deaths from the Eastern Ontario Regional Forensic Pathology Unit so that prevention strategies for these deaths can be developed. The analyses included examining the opioids involved and demographic characteristics of the individuals in these deaths so that possible risk factors for opioid-related deaths could be identified. A retrospective cross-sectional analysis of the full autopsy and toxicology data between 2011 and 2016 was conducted. Trends regarding the opioids involved in the death, all opioids reported in the toxicology reports and certain nonopioid drugs reported in the toxicology reports were examined. The distribution of opioid-related death by age-group and manner of death was also conducted. Two hundred seventy-four opioid-related deaths met the inclusion criteria and were examined. The majority of individuals overdosing were male. The most frequent age range for opioid-related deaths was 45 to 54 years with increasing deaths among individuals aged 55 years and older over the period studied. Fentanyl was responsible for most deaths overall when single or multiple opioids were involved. However, hydromorphone involvement was the only opioid to have a statistically significant increase over the time period. Analysis of nonopioid-related drugs revealed extensive use of antidepressants, benzodiazepines, and their metabolites. Accident was the most common manner of death throughout all age groups except for those aged 65 years or older, where suicide was most common.